Coupled Response of Bacterial Production to a Wind-Induced Fall Phytoplankton Bloom and Sediment Resuspension in the Chukchi Sea Shelf, Western Arctic Ocean - Uchimiya, Mario; Motegi, Chiaki; Nishino, Shigeto; Kawaguchi, Yusuke; Inoue, Jun; Ogawa, Hiroshi; Nagata, Toshi (Frontiers in Marine Science, 2016)
Heterotrophic bacterial abundance and production, dissolved free amino acid (DFAA) and dissolved combined amino acid (DCAA) concentrations, and other microbial parameters were determined for seawater samples collected at a fixed station (maximum water depth, 56 m) deployed on the Chukchi Sea Shelf, in the western Arctic Ocean, during a 16-day period in September 2013. During the investigation period, the sampling station experienced strong winds and a subsequent phytoplankton bloom, which was thought to be triggered by enhanced vertical mixing and upward nutrient fluxes. In this study, we investigated whether bacterial and dissolved amino acid parameters changed in response to these physical and biogeochemical events. Bacterial abundance and production in the upper layer increased with increasing chlorophyll a concentration, despite a concomitant decrease in seawater temperature from 3.2°C to 1.5°C. The percentage of bacteria with high nucleic acid content during the bloom was significantly higher than that during the prebloom period. The ratio of the depth-integrated (0–20 m) bacterial production to primary production differed little between the prebloom and bloom period, with an overall average value of 0.14 ± 0.03 (± standard deviation, n = 8). DFAA and DCAA concentrations varied over a limited range throughout the investigation, indicating that the supply and consumption of labile dissolved amino acids were balanced. These results indicate that there was a tightly coupled, large flow of organic carbon from primary producers to heterotrophic bacteria during the fall bloom. Our data also revealed that bacterial production and abundance were high in the bottom nepheloid (low transmittance) layer during strong wind events, which was associated with sediment resuspension due to turbulence near the seafloor. The impacts of fall wind events, which are predicted to become more prominent with the extension of the ice-free period, on bacterial processes and the dynamics of organic matter in the Chukchi Sea Shelf could have far-reaching influences on biogeochemical cycles and ecosystem dynamics in broader regions of the Arctic Ocean.